Problems of international Money, 1972-85. (International Monetary Fund, 1996)
This paper analyzes problems of international money. The paper highlights that there are three chief economic evils-starvation and poverty in the Third World, unemployment in industrial countries, and price inflation in the industrial countries that has been so fast as to be socially unacceptable at home and to complicate immensely social and economic adjustment in much of the rest of the world. The paper examines structural change and financial innovation in the international monetary system since 1972. It also analyzes exchange rate management and surveillance since 1972.